SAT0237 Dublin Uveitis Evaluation Tool (DUET): A Proposed Algorithm and Its Performance Evaluation for the Best Referral By Ophthalmologists of Acute Anterior Uveitis Patients with Possible Underlying Spondyloarthropathy. (23rd January 2014) - Haroon, M.; Ramasamy, P.; O'Rourke, M.; Murphy, C.; FitzGerald, O.
Abstract : Background: Recent reports claim that the prevalence figures of mostly undiagnosed underlying Spondyloarthropathy (SpA) is more than 60% among patients presenting with acute anterior uveitis (AAU). To date, there are no formal guidelines or referral pathways for AAU patients developed or endorsed by any international or national societies. Therefore, in a condition where significant delay in diagnosis is common, and where AAU may frequently be the first interaction with medical care, an opportunity to identify SpA early is often missed leading to less than ideal care. Objectives: The objectives of our study were: (1) to develop an assessment algorithm for referral from Ophthalmologists of appropriate AAU patients to Rheumatology that will aid the early diagnosis of the SpA; (2) to explore whether modifications of this novel algorithm might further improve sensitivity and specificity; and (3) to investigate the prevalence of undiagnosed SpA in patients presenting with AAU in a primary care ophthalmology setting. Methods: All consecutive patients attending emergency department of local ophthalmology hospital with AAU, but who did not have a known diagnosis of SpA, were eligible to partake in this study. Patients with any other known cause of AAU were excluded. The HLA-B27 status was checked in all patients, and assessment and onward referral was made as per a test algorithm which combined clinical features and HLA-B27. Patients without risk factors for SpA and who were HLA-B27 negative remained part of the study as a control group; these patients also underwent detailed rheumatologic evaluation. Results: 104 consecutive patients who attended the ophthalmology emergency department from September 2011 through to June 2012 were recruited. Mean age of the cohort was 42±15 years. and HLA- B27 was positive in 52.5%. According to the test algorithm, 71 out of 104 patients were referred to rheumatologists; 69 of them had complete rheumatologic assessment. After rheumatologic evaluation, 41.6% (n=42) of these patients were diagnosed with SpA as per ASAS classification criteria. Of these newly diagnosed patients, 64.3% had radiographic axial SpA. Non radiographic SpA patients were noted to have shorter duration of backache (p=0.03). Our test algorithm was noted to have: sensitivity 100%, specificity 53.5%, PPV 61% and NPV 100%. Further regression analysis revealed that algorithm version-1 could make the following improvements: sensitivity 95%, specificity 98%, PPV 97.5%, NPV 96.6%. Image/graph: Conclusions: 41.5% of patients presenting with idiopathic AAU have undiagnosed SpA. A simple to apply algorithm is described with excellent sensitivity and specificity that is currently being validated in an additional cohort. Disclosure of Interest: None Declared